2017
DOI: 10.1080/0142159x.2017.1391373
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking technology in medical education: A systematic review

Abstract: Overall, eye-tracking methodology has contributed significantly to the training, assessment, and feedback practices used in the clinical setting. The technology provides reliable quantitative data, which can be interpreted to give an indication of clinical skill, provide training solutions and aid in feedback and reflection. This review provides a detailed summary of evidence relating to eye-tracking methodology and its uses as a training method, changes in visual gaze behavior during the learning curve, eye-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 37 publications
0
113
0
Order By: Relevance
“…Simulation training is a well-recognised educational tool in medical and emergency personnel education that allow improvement of technical and non-technical skills [1719]. Eye-tracking technology was reported as effective instrument in order to complement the simulation training and the subjects performance assessment [20,21]. Recent publications show its effectiveness assessing or evaluating in simulating scenarios related to anaphylaxis or paediatric trauma [12,22].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training is a well-recognised educational tool in medical and emergency personnel education that allow improvement of technical and non-technical skills [1719]. Eye-tracking technology was reported as effective instrument in order to complement the simulation training and the subjects performance assessment [20,21]. Recent publications show its effectiveness assessing or evaluating in simulating scenarios related to anaphylaxis or paediatric trauma [12,22].…”
Section: Discussionmentioning
confidence: 99%
“…Eye-tracking data collected during pediatric trauma may build our understanding of situational awareness amongst trauma team members, which can be used to guide the development of future educational interventions. [4][5][6]…”
Section: Résumémentioning
confidence: 99%
“…Eye tracking is an established quantitative objective tool in the assessment of surgical skill . Observation of the gaze behaviour in surgeons has made it possible to differentiate between gaze patterns of novices and experts, simulated and live operations, and giving valuable information regarding the surgeon's cognitive load .…”
Section: Introductionmentioning
confidence: 99%
“…13 Eye tracking is an established quantitative objective tool in the assessment of surgical skill. 14,15 Observation of the gaze behaviour in surgeons has made it possible to differentiate between gaze patterns of novices and experts, [16][17][18] simulated and live operations, 19 and giving valuable information regarding the surgeon's cognitive load. 20 Original work by Hess and Polt 21 found that mean pupil dilation was a function of the level of difficulty, with subsequent studies of pupilometrics showing that pupil diameter increases with increasing task demands.…”
Section: Introductionmentioning
confidence: 99%